PENGETAHUAN IBU YANG MEMILIKI BAYI TENTANG IMUNISASI DI WILAYAH KERJA PUSKESMAS PARINGGONAN KECAMATAN HULU BARUMUN KABUPATEN PADANG LAWAS TAHHUN 2019 - DEDE MAYSARAH (LP2MTBM MAKARIOZ, 2020)
This research method is descriptive, using primary and secondary data conducted by distributing questionnaires to 85respondents, sampling using Cluster Sampling. This research was conducted in November to April. The results wereobtained based on the knowledge of the majority of knowledge Less as many as 47 respondents (55.29%), and a wellknowledgeableminority of 17 respondents (20%). Based on age, the majority aged 20 - 35 years as many as 67respondents (78.82%) and minority age of respondents < 20 years, namely 3 respondents (3.52%). Based on education, themajority of high school educated respondents were 54 respondents (63.52%) and a minority of higher education-educatedrespondents, namely 6 respondents (7.05%). Based on employment, the majority of respondents worked as Housewives(IRT) as many as 67 respondents (78.82%) and minority types of work respondents are as civil servants as many as 3respondents (3.52%). The knowledge of mothers who have babies about immunizations in the working area of ParinggonanHealth Center is in the category of less. It is expected that mothers who have babies will further increase their knowledgeabout immunizations.